ETIKA BISNIS, BUDAYA ORGANISASI, CORPORATE GOVERNANCE , KINERJA PERUSAHAAN DAN KOMITMEN ORGANISASI - Sunardi, Sunardi (Universitas Muhammadiyah Palembang, 2017)
ABSTRACT The purpose of this study was to examine the influence of business ethics and organizational culture on corporate governance and corporate performance that was moderated by organizational commitment. Methodology of research, this research was conducted on 11 banks which was conducting dual system operation (conventional and syariah) in Palembang City, research instrument by using questioner was 125 people respondent, answer statement tested validity and reliability with valid and reliable results with outer loading through two times of elimination. Data analysis used partial least square regression (PLS), Limitations of this study were the respondents who spend less time, so that filled questionnaires in others and did not necessarily understand the contents of the questionnaire, in addition to the number of respondents and the limited number of samples were resulting in less satisfactory research. Implication of research results by banks were as things that must be implemented by banks in order to improve performance and high competitiveness. The result of the research was business ethics that had a significant positive effect on corporate governance, organizational culture had a significant positive effect on corporate governance, corporate governance had no significant positive effect on company performance, and organizational commitment could not moderate the influence of corporate governance on company performance